Evolution of global value chains research - Skirko, Natallia I. (Journal of the Belarusian State University. Economics, 2022)
The article is devoted to the analysis of economic research on global value chains. The relevance of the research topic is connected not only with the evolution of mechanisms for building production chains on an international scale, but also with the evolution of the analysis of this process. The object of the study is the ways of building international production relations, inter-firm and inter-country, as conditions for the growth of international trade. The subject of the study is the evolution of research related to the construction of chains. The purpose of this study is to consider the sequence of formation of the conditions of globalisation of value chains. Тhe author proves the regularity of fragmentation, participation in transactions involving other people’s chains or organising their own, where it will be necessary to search for the most specialised performers. The hypothesis is an evidence of the emergence of factors of the stability of value chains over time.